Should Good Samaritans Be Protected by Law (Beijing review, 2015)
The Beijing Municipal Government has recently issued draft regulations that mean to encourage more people to help those who need first aid, including seniors suddenly stricken by certain condi- tions. These regulations come amid a spate of reports of well-intentioned individuals who come to the aid of elderly people and end up being subject to slander or worse, black- mail. If passed, the local legislation will offer legal support for these good Samaritans so that they need not worry about being blackmailed after doing a good deed. The document provides that people who per- petrate unfounded slander and blackmail against those that help them shall be held legally accountable.